2016
DOI: 10.1111/jog.13212
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo cardiomyopathy after cesarean section: A case report and literature review

Abstract: Takotsubo cardiomyopathy (TCM) is clinically identical to acute myocardial infarction. We report an unusual case of TCM and review similar cases in pregnant women. A young woman with no pre-existing cardiovascular risk factors suffered sudden dyspnea during a cesarean section. Electrocardiography (ECG) showed T-wave inversion. We observed acute lung edema and left ventricular systolic dysfunction on echocardiography. A cardiac catheterization diagnosed TCM. We reviewed 20 cases of TCM; 17 cases occurred during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…One-third of these cases were found during caesarean section. All patients with Takotsubo cardiomyopathy recovered between 4 days and 3 months, as in non-pregnant patients with Takotsubo cardiomyopathy 42…”
Section: Other Cardiomyopathiesmentioning
confidence: 85%
“…One-third of these cases were found during caesarean section. All patients with Takotsubo cardiomyopathy recovered between 4 days and 3 months, as in non-pregnant patients with Takotsubo cardiomyopathy 42…”
Section: Other Cardiomyopathiesmentioning
confidence: 85%
“…Most of the reported TTS cases in pregnant women happened after childbirth with caesarean delivery, but TTS has also been reported in women during pregnancy. Similar to non‐pregnant patients with TTS, recovery occurred between 4 days and 3 months 59 …”
Section: Specific Cardiomyopathiesmentioning
confidence: 68%
“…The second possibility regards the hyperadrenergic state. A study mentioned above demonstrated that of 20 patients with pregnancy‐associated TTS, TTS occurred in the intraoperative period in five patients, a high percentage . Indeed, studies showed a close association between TTS and the hyperadrenergic status .…”
Section: Discussionmentioning
confidence: 97%
“…A study mentioned above demonstrated that of 20 patients with pregnancy-associated TTS, TTS occurred in the intraoperative period in five patients, a high percentage. 11 Indeed, studies showed a close association between TTS and the hyperadrenergic status. 1,10,12 PE is also associated with increased sensitivity to endogenous adrenaline.…”
Section: Discussionmentioning
confidence: 99%